A Review on Design of Integrated Healthcare Model through Performance Excellence Methodologies - Ramayanam, Srideepti; Acharayulu, G.V.R.K; Prasad, V.M. (American International Journal of Multidisciplinary Scientific Research, 2018)
Cost based care is evolving as a resolution to address increasing Healthcare costs, and to address the problem of clinical inefficiencies. ‘Cost based care’ therefore is designed to be patient centric. While ‘Cost based care’ helps in addressing the challenge of rising costs and making the care more affordable, it  comes with its own set of challenges for providers as they are paid for better patient outcomes in an evidence based way.  In the regimen of ‘Cost based care’ providers are grappling with reduced reimbursements. Providers are also required to track wide variety of measures to make the care more evidence based. Operations transformation for a healthcare systems means that it makes the processes, efficient, flexible and innovative to suit patient centric treatment models. To achieve this transformation by excluding wastes out of system, make the processes much more efficient, implementation of digital systems across the value chain of the hospital have become the area of focus. Shared Services alteration is a subclass of administrational transformation. It is has a lot of potential to smoke out costs, making operational processes much more efficient by rationalizing functions, like Human Resources, Pathology, Radiology, IT and Supply chain services at Hospitals. Administrational transformation aims to flush out costs, bring transformation in revenue cycle, and focus on Patient centric treatment modules. By implementing data visualization dashboards across the services would enable transparency and trust for patients.